Inequality of Interregional Development in Riau Indonesia; Panel Data Regression Approach - Hidayat, Muhammad; Darwin, Ranti; Hadi, M. Fikry (International Journal of Economics and Financial Issues, 2018)
This study aims to analyze the trends and factors of inequality of inter-regional development in Riau Province period 2011-2016. Analyzer used in the form of Index Theil, Bonet Index, and regression of panel data with fix effect model. The analysis result with Theil and Bonet Index shows the decreasing trend of Interregional Development Inequality, and the source of inequality comes from within the development area (within) with the percentage of 58% -68%. The result of fixed effect model regression states that the variable of fiscal decentralization, government expenditure, HDI, and economic growth have negative and significant relation to inequality. While the variables of natural resource differences have a positive and statistically insignificant relationship. Keywords: Inequality Development, Data Panel Regression, Riau JEL Classifications: D63, O53, R58